Calculus 8th Edition

Published by Cengage
ISBN 10: 1285740629
ISBN 13: 978-1-28574-062-1

Chapter 6 - Inverse Functions - 6.4* General Logarithmic and Exponential Functions - 6.4* Exercise - Page 464: 35



Work Step by Step

Given: $y =x^{x}$ Taking logarithmic on both sides of the function$y =x^{x}$. Use logarithmic property $ln(x^{y})=ylnx$ $lny=xlnx$ Take implicit differentiation with respect to $x$. Apply product rule of differentiation. $\frac{d}{dx}(lny)=\frac{d}{dx}(xlnx)$ $\frac{1}{y}\frac{d}{dx}(y)=x\frac{d}{dx}(lnx)+lnx\frac{d}{dx}(x)$ $\frac{d}{dx}(y)=y[x\times(\frac{1}{x})+lnx\times1]$ Hence, $y'=x^{x}(1+lnx)$
Update this answer!

You can help us out by revising, improving and updating this answer.

Update this answer

After you claim an answer you’ll have 24 hours to send in a draft. An editor will review the submission and either publish your submission or provide feedback.